What is a gene? From molecules to metaphysics - Rolston, Holmes, 1932-2025, author; Kluwer Academic Publishers, publisher (Colorado State University. Libraries, 2006)
Mendelian genes have become molecular genes, with increasing puzzlement about locating them, due to increasing complexity in genomic webworks. Genome science finds modular and conserved units of inheritance, identified as homologous genes. Such genes are cybernetic, transmitting information over generations; this too requires multi-leveled analysis, from DNA transcription to development and reproduction of the whole organism. Genes are conserved; genes are also dynamic and creative in evolutionary speciation - most remarkably producing humans capable of wondering about what genes are.
Springer http://dx.doi.org/10.1007/s11017-006-9022-9.
Keywords: mendelian; intentionality in genes; genetic identity; cybernetic genes; molecular; searching genes